The Relation of Direct and Indirect Taxes on Government Revenue collection of Nepal - Hari Prasad Adhikari,; Surya Prasad Poudel, (Nepalese Journal of Management Research, 2025)
The government revenue is the basic sources for economic development, social securities, national security, and etc. government of the country. Government has to collect revenue for the achievement of stipulated objectives. This research has been organized to understand the collection trend of total revenue, direct and indirect taxes of Nepal Government and it analyzes the correlation of direct and indirect taxes with total revenue. Trend graph, descriptive statistics and Pearson correlation have been deployed for analysis purpose. The 20 years data from 2003/004 to 2022/023 have been taken from economic survey of Nepal Government. The analysis has shown that, total revenue, direct and indirect taxes found in incremental trend. The total revenue and indirect tax has been found more fluctuating than direct tax. Taxes revenue have higher correlation with total revenue of Nepal. The higher correlation of taxes revenue with total tax revenue refers the Government of Nepal is unable to utilize alternative sources of revenue of Nepal. The Government of Nepal should raise their revenue from formulation of revenue collection policies from tax and nontax sector. On the other hand the government of Nepal should raise revenue from the policy of proper application of natural resources, increased in government investment, search alternative sources of government revenue, etc.